NK cells in pancreatic cancer demonstrate impaired cytotoxicity and a regulatory IL-10 phenotype - Marcon, Francesca (Oncoimmunology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most common tumor subtypes and remains associated with very poor survival. T cell infiltration into tumor tissue is associated with improved clinical outcome but little is known regarding the potential role of NK cells in disease control. Here we analyze the phenotype and function of NK cells in the blood and tumor tissue from patients with PDAC. Peripheral NK cells are present in normal numbers but display a CD16(hi)CD57(hi) phenotype with marked downregulation of NKG2D. Importantly, these cells demonstrate reduced cytotoxic activity and low levels of IFN-γ expression but instead produce high levels of intracellular IL-10, an immunoregulatory cytokine found at increased levels in the blood of PDAC patients. In contrast, NK cells are largely excluded from tumor tissue where they display strong downregulation of both CD16 and CD57, a phenotype that was recapitulated in primary NK cells following co-culture with PDAC organoids. Moreover, expression of activatory proteins, including DNAM-1 and NKP30, was markedly suppressed and the DNAM-1 ligand PVR was strongly expressed on tumor cells. As such, in situ and peripheral NK cells display differential features in patients with PDAC and indicate local and systemic mechanisms by which the tumor can evade immune control. These findings offer a number of potential options for NK-based immunotherapy in the management of patients with PDAC.